Implementation of the Mobile School Program in Increasing the Quality of Education - Agdila, Agik; Lian, Bukman; Putra, Muhammad Juliansyah (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe how the implementation of the driving school program in improving the quality of education at SMAN South Sumatra. This research was conducted at the South Sumatra High School located in Jakabaring, Palembang, South Sumatra. implementation in this research activity, namely for two months from November 10 to December 10, 2022. The research is a type of qualitative research with an analytical descriptive flow that has the aim of proving various kinds of norms and theories regarding the quality of education in terms of the Pancasila Strengthening Project Bangunlah jiwa and Body and its application to the object of research. In qualitative research, the information obtained is generally in the form of words, and descriptive, and the majority is not in the form of numbers. Collecting data and information obtained by researchers while in the field by obtaining direct surveys and documentation and research results, almost 90% of students can implement the driving school program to improve education at SMAN South Sumatra from the results of the researcher’s evaluation.